Mitochondrial Fission Is Required for Angiotensin II-Induced Cardiomyocyte Apoptosis Mediated by a Sirt1-p53 Signaling Pathway - Jia Qi; Jia Qi; Feng Wang; Ping Yang; Xuelian Wang; Renjie Xu; Jihui Chen; Yanggang Yuan; Zhaoyang Lu; Zhaoyang Lu; Junli Duan (Frontiers Media S.A., 2018)
Hypertension-induced cardiac apoptosis is a major contributor to early-stage heart-failure. Our previous studies have found that p53-mediated mitochondrial fission is involved in aldosterone-induced podocyte apoptosis. However, it is not clear that whether p53-induced mitochondrial fission is critical for hypertensive Angiotensin II (AngII)-induced cardiomyocyte apoptosis. In this study, we found that inhibition of the mitochondrial fission protein Drp1 (dynamin-related protein 1) by Mdivi-1 prevented cardiomyocyte apoptosis and cardiac remodeling in SHRs. In vitro we found that treatment of cultured neonatal rat cardiomyocytes with AngII induced Drp1 expression, mitochondrial fission, and apoptosis. Knockdown of Drp1 inhibited AngII-induced mitochondrial fission and cardiomyocyte apoptosis. Furthermore, AngII induced p53 acetylation. Knockdown of p53 inhibited AngII-induced Drp1 expression, mitochondrial fission, and cardiomyocyte apoptosis. Besides, we found that Sirt1 was able to reverse AngII-induced p53 acetylation and its binding to the Drp1 promoter, which subsequently inhibited mitochondrial fission and eventually attenuated cardiomyocyte apoptosis. Collectively, these results suggest that AngII degrades Sirt1 to increase p53 acetylation, which induces Drp1 expression and eventually results in cardiomyocyte apoptosis. Sirt1/p53/Drp1dependent mitochondrial fission may be a valuable therapeutic target for hypertension induced heart failure.